Paid work, life-work and leisure: a study of wellbeing in the context of academic lives in higher education. Issue 1 (2nd January 2016) - Siddiquee, A.; Sixsmith, J.; Lawthom, R.; Haworth, J.
Abstract : Living, working, leisure, and well-being are of increasing concern to educators, policy-makers, governments and people generally. The aim of this research note is to investigate the relationships between paid work, life work and leisure in terms of well-being associated with activity. The research used a modified experience sampling method for a one-week period with a staff group based in an educational institution. The data collection period included a bank holiday (three days holiday and four days work). A mobile phone was used to collect data eight times a day, over seven days, on activity, enjoyment, interest, visual interest, challenge, skill and happiness. Data analysis showed a significant correlation between enjoyment and happiness; enjoyment and interest; and visual interest, which also correlated with happiness. Enjoyment and happiness were experienced more in leisure than in paid work and life work. Level of enjoyment was greatest when skills were greater than moderate challenge in activity, though high enjoyment was more frequent when moderate and high challenge were met with equal skills (satisfying conditions of 'flow'). High enjoyment came as much from paid work as from leisure. The findings replicate and extend earlier research, and the research note emphasises the importance of measures of enjoyment in the investigation of national wellbeing.